Hemodynamic Assessment via Echocardiography During Propofol Anesthetic Induction in Healthy Dogs - Thais Cabral de Oliveira; Guilherme Andraus Bispo; Laura Beatriz de Socorro Poleto; Francisco Dantas de Maio Martinez; Max Túlio Rocha de Souza; Lais Calazans Menescal Linhares; Marilda Onghero Taffarel; Wagner Luís Ferreira; e Paulo Sérgio Patto dos Santos (Veterinary Medicine International)
Conclusion and Clinical Relevance: Propofol was a safe anesthetic-inducing agent, maintaining stable hemodynamic indices during anesthetic induction at the used rate.